A Cryptographic Algorithm Based On Aes Cipher Andnondeterministic Algorithm Approach For Key Generation - Ofosu, Amoah Emmanuel; Kester, Quist-Aphetsi; Anyanewah, Attah Josephine Akosua (2019 International Conference on Computing, Computational Modelling and Applications (ICCMA), 2019)
E-commerce and the financial services sector continue to rely hugely on the internet towards performing their activities. The need for a secured and protected environment to support the use of the internet has become critical in our time. A strong encryption system is required to protect data stored at a maximum level. The need for a strong and faster encryption algorithm to provide anenhanced network security has become relevant in recent time. This paper addresses the above issue by using a cryptographic method by applying the AES 256-bit algorithm (Rijndael) method of encryption and Non-Deterministic Algorithm (Monte- Carlo Simulation). An algorithm for encrypting and decrypting was built mainly for encrypting and decrypting documents coupled with non-deterministic approach for key generation. The system was designed, developed and the results obtained.